2017
DOI: 10.1038/s41598-017-01427-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deficiency accelerates lumbar facet joints arthritis

Abstract: Dramatic increase in the prevalence of lumbar facet joint (LFJ) arthritis in women around the age of menopause indicates a protective role for estrogen in LFJ arthritis. To date, there is no evidence for this indication and the mechanism of such an effect remains poorly understood. In this study, ovariectomized (OVX) mice were used to mimic the estrogen-deficient status of post-menopausal women. Micro-CT and immunohistochemistry was employed to assess the morphological and molecular changes in ovariectomy-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
3
22
0
1
Order By: Relevance
“…Similarly, ovariectomized mice displaying enhanced loss and collapse of cortical bone in facet joints, rapidly developed severe cartilage degeneration. Interestingly, the development of an osteoarthritic phenotype could be rescued by estrogen treatment that prevented progressive cortical bone loss [ 23 ]. While cross-sectional and longitudinal clinical imaging data of FJOA are crucially lacking, our results suggest that loss of cortical plate thickness is a prominent feature in human disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ovariectomized mice displaying enhanced loss and collapse of cortical bone in facet joints, rapidly developed severe cartilage degeneration. Interestingly, the development of an osteoarthritic phenotype could be rescued by estrogen treatment that prevented progressive cortical bone loss [ 23 ]. While cross-sectional and longitudinal clinical imaging data of FJOA are crucially lacking, our results suggest that loss of cortical plate thickness is a prominent feature in human disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors have been proposed for FJD, such as age, overweight, and smoking [ 1 , 5 ]. In recent studies, researchers found FJD in ovariectomy (OVX) mice [ 6 , 7 ], which indicated that estrogen deficiency may also be a risk factor for FJD. Cartilage is sensitive to sex hormones [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptors are present in several cells in the joints, including cartilage cells, subchondral bone cells, and synovial cells, and the expression of estrogen receptors increases in osteoarthritis patients [22][23][24]. Experiments using ovariectomized animal models showed that a continued state of low estrogen concentration leads to decreased intra-articular subchondral bone mass, increased interface of the subchondral cavity, and progression of severe cartilage degradation [25]. Altogether, women experience rapid joint degeneration around the ages of 50-75 years after menopause, and show higher prevalence, frequency, and severity of osteoarthritis than men [6,15].…”
Section: Discussionmentioning
confidence: 99%